An Information System Study on the Registration System of the Rizal High School - Africa, Gil.; Amilbangsa, Gil.; Blancada, Vic.; Flores, Rommel; Raymundo, Freddie; Umali, Caloy (Diliman, Quezon City College of Engineering, 1986)
Rizal High School is the first provincial high school in the Philippines. It was founded in October 1, 1902, with a population of 28 students under the guidance of three American teachers. Mr. Stewart Laughlin was the first principal. At the time of its foundation up to 1913, Rizal High School held classes in rented rooms, near the municipal hall, at a cost of 15 dollars per annum. The payment of the rent was provided by then Governor Ambrosio Flores. In 1914, a parcel of lain in Caniogan, Pasig was purchased by the provincial government to serve as the campus of the high school. Presently located at the same site, the school facilities constructed over the years are spread over a 63,704 square meter campus. The school employs the services of not less than 400 teachers to provide low cost education to 15,000 students, the largest student population of any high school in the Philippines and Asia. The student body is broken down into sections with an average number of 45 students each, with 95 sections for freshmen, 85 for sophomores, 75 for juniors and 65 for senior students. Students are assigned to sections on the basis of their academic performance, as reflected in form 138, the report card. Students are ranked from highest to lowest and divided into sections according to their ranking, with students of approximately similar averages going into the same sections. For incoming freshmen, the average of Math and English as reported in their elementary report cards is used for ranking, except for valedictorians and salutatorians who are automatically assigned to sections 1 and 2, which are honor sections with different academic loads. Regular and transfer students are ranked according to their academic average and mobility of sections is possible except for entry into the honor sections. The current registration system deals with this task along with others on a manual and labor intensive basis. Coupled with the enormous amount of information processed from the large student body, there is a need for examining the system, which has existed for many years by this time, and perhaps improve upon it or change it for economic reasons.
Feasibility Study
Typescript
Submitted in partial fulfillment of the course requirements in IE 154 : Information Systems I
Keywords: Rizal High School; Recording and registration; Student affairs services; Information resources management